Interrelationship of Food Wastage and Sustainable Development: A Review - Eric D. Bimmoy (CV. Literasi Indonesia, 2022)
This paper aims to examine the interrelationship of food consumption and designing a sustainable community. Japan has achieved its economic vestige through healthy economic development and technological opportunity, resource utilization, and the well-being of the community and citizens. Related to creating a sustainable community, it requires a coordinated joined approach involving a wide range of resources and stakeholders. To attain zero food waste community, resource mobilization is needed that promotes sustainable food consumption. Resource mobilization is the process of getting resources from resource providers, using different mechanisms, to implement the organization's work for achieving the pre-determined organizational goals. Technology is much needed to come up with efficient mechanization and technologies in preventing, reducing, and reutilizing food wastes. During the design process, it is essential to understand that having the same level of understanding should be established, in terms of common current issues.